Three conceptualizations of hybrid management in hospitals. Issue 5 (7th July 2014) - Ingo Bode and Professor Mike Dent, Dr; Byrkjeflot, Haldor; Kragh Jespersen, Peter
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to bring the discussion on the relationship between management and medicine a step forward by focussing on: first, how the notion of hybrid and hybridity has been used in the literature on healthcare management. Second, the authors have mapped the alternative ways that the concept have been used in order to conceptualize a more specific set of possible combinations of managerial and professional roles in healthcare management. Hybrid management is a topic that ought to be important for training, communication among researchers and for identifying areas of future research: in management, in healthcare reforms, in sociology of professions and in theory of organizations. Design/methodology/approach – The authors provide a systematic literature review in order to map the various conceptualizations of hybrid management. The authors have searched for "hybrid leadership, " "hybrid management" combined with hospitals and health care in a whole range of journals, identified in Google scholar, Academic Search Premier, Academic Research Library and Sage Publication. The authors have also used already existing literature reviews. The search has resulted in more than 60 articles and book titles that have been classified according to whether they make a fit with three alternative ways of conceptualizing hybrid management. The authors are aware that they might have missed some relevant literature but the literature included is quite comprehensive. Findings – In the literature the authors have found three conceptualizations of management. The clinical manager who combines professional self-governance with a general management logic. The commercialized manager who combines professional self-governance with an enterprise logic. The neo-bureaucratic manager who combines self-governance with a neo-bureaucratic logic. Originality/value – In most analyses of hybridity in management and organization the notion of hybrid has been used in a rather superficial way. By mapping the various uses of hybrid in the literature and suggest how a professional logic may be combined with a set of alternative logics of management the authors provide a platform for developing the concept of hybrid management into a more useful tool for analyses of changes in healthcare management.